2023
DOI: 10.3847/1538-4365/acdee1
|View full text |Cite
|
Sign up to set email alerts
|

A Data Science Platform to Enable Time-domain Astronomy

Abstract: SkyPortal is an open-source software package designed to discover interesting transients efficiently, manage follow-up, perform characterization, and visualize the results. By enabling fast access to archival and catalog data, crossmatching heterogeneous data streams, and the triggering and monitoring of on-demand observations for further characterization, a SkyPortal-based platform has been operating at scale for >2 yr for the Zwicky Transient Facility Phase II community, with hundreds of users, containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…We ingested the GBM localization map (Goldstein et al 2022) into Fritz (van der Walt et al 2019), the ZTF instance of SkyPortal (van der Walt et al 2019;Coughlin et al 2023), an interactive tool designed to plan and schedule target-ofopportunity observations for ZTF. The observing plan was generated using gwemopt (Coughlin et al 2019) by taking the healpix Fermi-GBM localization map, slicing the sky map into predefined tiles of the size and shape of the ZTF field of view, determining which fields have the highest enclosed probability, and optimizing observations based on air mass and visibility windows.…”
Section: Zwicky Transient Facilitymentioning
confidence: 99%
“…We ingested the GBM localization map (Goldstein et al 2022) into Fritz (van der Walt et al 2019), the ZTF instance of SkyPortal (van der Walt et al 2019;Coughlin et al 2023), an interactive tool designed to plan and schedule target-ofopportunity observations for ZTF. The observing plan was generated using gwemopt (Coughlin et al 2019) by taking the healpix Fermi-GBM localization map, slicing the sky map into predefined tiles of the size and shape of the ZTF field of view, determining which fields have the highest enclosed probability, and optimizing observations based on air mass and visibility windows.…”
Section: Zwicky Transient Facilitymentioning
confidence: 99%
“…The complexity of our observing program and the necessity of responding in real time to alerts and incoming data require that we centralize all of our tools for planning observations, monitoring data, vetting targets, and reporting results in a single location that is accessible to all team members at all times. Current transient surveys and large follow-up programs use similar systems, including the Asteroid Terrestrial-impact Last Alert System (ATLAS) Transient Science Server (Smith et al 2020), the Global Rapid Advanced Network Devoted to the Multi-messenger Addicts' Interface and Communication for Addicts of the Rapid follow-up in multi-messenger Era (Antier et al 2020a), the Global Relay of Observatories Watching Transients Happen Marshal (Kasliwal et al 2019), the Global Supernova Project's Supernova Exchange (Howell & Global Supernova Project 2017), the Public ESO Spectroscopic Survey of Transient Objects Marshall (Smartt et al 2015), the Young Supernova Experiment's YSE-PZ (Coulter et al 2023), and the Zwicky Transient Facility's Fritz (based on SkyPortal; Coughlin et al 2023).…”
Section: Target and Observation Managermentioning
confidence: 99%
“…We also triggered Swift target-of-opportunity observations and confirmed that the X-ray flux had increased by three orders of magnitude relative to the quiescent level (Bellm 2021b). We used a customized Skyportal (van der Walt et al 2019;Coughlin et al 2023) instance ("Fritz") for managing follow-up data.…”
Section: Discovery Of the Outburstmentioning
confidence: 99%